2019
DOI: 10.3390/ma12040674
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Limited Nucleation of NiSi/SiC Core-Shell Nanowires by Hot-Wire Chemical Vapor Deposition

Abstract: This work demonstrated a growth of well-aligned NiSi/SiC core-shell nanowires by a one-step process of hot-wire chemical vapor deposition on Ni-coated crystal silicon substrates at different thicknesses. The NiSi nanoparticles (60 to 207 nm) acted as nano-templates to initially inducing the growth of these core-shell nanowires. These core-shell nanowires were structured by single crystalline NiSi and amorphous SiC as the cores and shells of the nanowires, respectively. It is proposed that the precipitation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…where R sh is the sheet resistance, C is the correction factor, L T is the effective transfer length, r is the radius of the inner circle, which was fixed at 80 mm, and s is the gap space, which was split as 8,12,16,20,24,32,40, and 48 mm. R sh and L T can be determined via a linear fit of R T at the different gap space values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where R sh is the sheet resistance, C is the correction factor, L T is the effective transfer length, r is the radius of the inner circle, which was fixed at 80 mm, and s is the gap space, which was split as 8,12,16,20,24,32,40, and 48 mm. R sh and L T can be determined via a linear fit of R T at the different gap space values.…”
Section: Resultsmentioning
confidence: 99%
“…Kwang et al studied the interfacial properties of NiSi films deposited by using atomic layer deposition [11]. Mahdi et al reported well-aligned NiSi/SiC core-shell nanowire growth by hot-wire chemical vapor deposition to enhance the electrical properties of NiSi [12]. Koichi et al introduced a cyclic deposition process using molecular beam epitaxy (MBE) to grow NiSi for low-resistance films [13].…”
Section: Introductionmentioning
confidence: 99%
“…Other common technique, chemical vapor deposition (CVD) is a technique for deposition nanostructured thin film on substrates with very high temperature using precursor gases [22]. Insertion of hot-filament in to the CVD technique helps to deposit nanocrystalline of nanostructured thin film at lower substrate temperature as hot-filament chemical vapor deposition (HFCVD) technique [18,[23][24][25][26][27]. The HFCVD process employs the heated filament to decompose Deposition of Silver Nanoparticles on Indium Tin Oxide Substrates by Plasma-Assisted Hot… DOI: http://dx.doi.org /10.5772/intechopen.94456 the precursor species and deposit nanostructured film on the substrate.…”
Section: Plasma-assisted Hot-filament Evaporationmentioning
confidence: 99%
“…In addition, a precision mold is also time-consuming to fabricate. The model molding technology has developed rapidly in recent years, and the common microstructure component model molding technologies at present include plastics micro-injection molding [8,9], micro-thermoforming [10,11,12], micro-casting [13,14,15], and micro/nano imprinting [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. While the aforesaid technologies have their characteristics and merits, most of them require molds for micro-molding processing.…”
Section: Introductionmentioning
confidence: 99%